Calibration of the Crack Initiation Model in HDM 4 on the Highways and Primary Urban Streets Network in Macedonia - Slobodan Ognjenovic, Zoran Krakutovski, Nikolai Vatin (Procedia Engineering 117(1), 564-572, 2015)
The World Bank HDM4 model has been developed on the basis of the researches carried out in Brazil and in South Africa. Those researches lead to the derivation of models regarding almost all types of damage which can occur on the roads, but in order to use them worldwide, it is necessary to adjust them to the local conditions (traffic load, climate, construction specificities, maintenance level etc.). The theme of this research is essential for the development of urban areas. This paper presents the results of the researches in view of the definition of the calibration coefficient of the crack formation model in HDM4.
Keywords: urban area, crack initiation, HDM 4, calibration, maintenance, pavement management, urban highways, urban streets